Thyroid Hormones within the Normal Range and Cardiac Function in the General Population: The EPIPorto Study - Neves, JS (2021)
Background: Hypothyroidism and hyperthyroidism are associated with marked changes in cardiac structure and function. However, the association of thyroid function within the normal range with cardiac structure and function in the general population remains uncertain. Methods: Eight hundred thirty-five subjects aged ≥45 years from the EPIPorto cohort (evaluation between 2006 and 2008) were cross-sectionally analyzed. We excluded participants with TSH, free T4 (FT4), or free T3 (FT3) outside of the reference range or with self-reported cardiovascular or thyroid disease. Cardiac structure and function were evaluated by echocardiography. We used linear regression models unadjusted and adjusted for sex and age (model 1), and sex, age, BMI, diabetes, hypertension, and smoking (model 2). Nonlinear associations were assessed using restricted cubic splines. Results: The mean age was 61.5 years (SD 10.5); 61.1% of the patients were women. In the adjusted model 2, heart rate was positively associated with FT3; diastolic blood pressure was positively associated with TSH; LV end-diastolic and end-systolic volumes were inversely associated with TSH, and ejection fraction was nonlinearly associated with FT3, with higher ejection fractions near the limits of the reference range. Left ventricle (LV) posterior wall thickness was nonlinearly associated with FT4 in the adjusted model 1, with a greater thickness near the limits of the reference range. Regarding diastolic function, no significant associations were observed in adjusted models. Conclusions: Thyroid function within the reference range was associated with heart rate, blood pressure, cardiac structure, and function. Increasing thyroid function (lower TSH, higher FT4, or higher FT3) was associated with a higher heart rate, a lower diastolic blood pressure, and larger LV volumes. LV wall thickness and ejection fraction had a U-shaped association with thyroid hormones.